Etude statistique de la pêche au niveau des différents ports de la Wilaya Maritime de Mostaganem (2008 à 2017). - Ladjal, Fatima; Brahmi, Khadija (My University, 2018)
At the end of this work, essentially devoted to the study of fishing and its statistics at the level of the western Algerian of the three ports of Wilaya maritime Mostaganem, concerning respectively the ports, sidi lakhdar, central and port of salamander it appeared to us essential to recall our main results, before presenting our recommendations and the research perspectives that we wish to develop in the future. This work, largely based on surveys and field investigations, personal commercial fishery statistics, and those from the relevant departments (DPRH), concludes that the fishing fleet is continuous except for small trades with decreasing from 2008. The five ports show a significant dominance of small pelagic landings, compared to other major groups, to a lesser extent to Demersals and Crustaceans, but which, on the other hand, have a higher economic value. On the other hand it is the port of Mostaganem despite a fleet smaller in number that has the highest catches in white fish, crustaceans and cephalopods.
Keywords: Ouest algérien; Flottille; Débarquements; Assemblage.; West Algeria; Flotilla; Landings; Assembly.